2011
DOI: 10.1007/s10157-011-0578-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin level accurately reflects antioxidant potentials in idiopathic nephrotic syndrome

Abstract: Our results suggest that decreased antioxidant potentials caused by hypoalbuminemia in INS may contribute to an aberrant immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Polanco et al ( 30 ) found that the prognosis may be good in patients whose proteinuria reached 12 g/24 h. The present study did not find that proteinuria within the range of NS had any significant influence on the prognosis; however, the risk of end-point event occurrence in patients with serum albumin <25 g/l increased by 3.195-fold. Kaneko et al ( 31 ) identified that biological antioxidant potential (BAP) was closely correlated with the serum albumin concentration in patients with idiopathic nephrotic syndrome, and decreased BAP may aggravate the inflammatory response. Roche et al ( 32 ) also found that serum albumin is the most abundant antioxidant in the living body, and therefore hypoalbuminemia may reduce the ability of the body to repair oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Polanco et al ( 30 ) found that the prognosis may be good in patients whose proteinuria reached 12 g/24 h. The present study did not find that proteinuria within the range of NS had any significant influence on the prognosis; however, the risk of end-point event occurrence in patients with serum albumin <25 g/l increased by 3.195-fold. Kaneko et al ( 31 ) identified that biological antioxidant potential (BAP) was closely correlated with the serum albumin concentration in patients with idiopathic nephrotic syndrome, and decreased BAP may aggravate the inflammatory response. Roche et al ( 32 ) also found that serum albumin is the most abundant antioxidant in the living body, and therefore hypoalbuminemia may reduce the ability of the body to repair oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is a routine marker reflecting both nutritional status and systemic inflammation, while the synthesis of albumin can be suppressed by systematic inflammation and malnutrition. Recent studies have demonstrated that serum albumin functions as an antioxidant in the host defense mechanism . The ALB‐dNLR (albumin‐dNLR) score consists of the serum albumin and derived neutrophil to lymphocyte ratio, indicating nutritional status and inflammatory conditions that are associated with the disease activity of RA patients, while there is no investigation about the associations between ALB‐dNLR score and disease activity in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, serum albumin levels showed a significant negative association with high d-ROM levels in men, but not in women. Although a relationship between albumin and BAP has been reported in general population [27] and in patients with nephrotic syndrome [35], a relationship between albumin and d-ROMs in men has not been demonstrated previously. What causes the gender difference in the association between serum albumin and d-ROMs should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%